Investigating Trends and Future Research SMEs Performance: Perception from Analysis Bibliometrics - Nanang Rusliana; Aso Sukarso; Dwi Hastuti LK; Asep Muhammad Adam; Galih Nugraha (Jurnal Bisnis dan Kewirausahaan, 2025)
This research explores the scientific activities and general trends of SMEs performance. Bibliometrics analysis was used against 456 articles from 2000 to 2022 to see the general perspective of SMEs performance. The database used to collect data is Scopus with the search keyword "SMEs performance". Open Refine is used for data cleaning and harmonization. VOSviewer is then used for visualization and discussion. Based on the analysis results, 2020 is the year with the most publications. Ali Z. is the most prolific and influential writer in research. School of Business Management, Universiti Utara Malaysia, Malaysia, became affiliated with the most research. Malaysia is the country with the most research. The most active source is Sustainability (Switzerland). The Reference from Cenamor et al. in 2019, titled "How Entrepreneurial SMEs Compete via Digital Platforms: The Roles of Digital Platform Capability, Network Capability and Ambidexterity" is the reference with the most citations. Keywords SMEs performance is the most dominant keyword in SMEs research performance. This research provides detailed contributions and addresses gaps that future research must fill. This research also presents the analysis results for evaluating SME performance.